Dream-Inspired Art, Comparing Human and AI Approaches - Nakasato, Yasuhito (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2024)
This article discusses how I documented my dreams for two months, with the goal of uncovering how dreams are stored in my brain and gaining insight into the unconscious processes that lead to their creation. In exploring the relationship between dreams and art, I sought to understand the creative potential of dream-inspired art. Informed by my exploration I created art inspired by my dreams using Adobe Photoshop and Dall-E, an artificial intelligence tool. By comparing the aesthetic qualities of my digital art with those generated by Dall-E, I share the insights I have gained into the potential for AI in the creative process. This artistic exploration has broader implications for our understanding of the creative process, the role of the unconscious in art, and the relationship between humans and AI. Future research could further explore the potential for dream-inspired art and the role of AI in the creative process.